Perlindungan Hukum Preventif terhadap Merek Dagang di Indonesia Berdasarkan Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis - Slamet Pribadi; Dwi Seno Wijanarko (Universitas Kuningan, 2022)
The research objective is to identify and analyze the factors that must be considered in preventive efforts. This study uses a normative juridical approach. Normative legal research is a procedure and method of scientific research to find the truth based on the scientific logic of law from a normative perspective. The result of the research is that preventive legal protection provides protection for legitimate trademark owners. Preventive legal protection is a form of protection that leads to actions that prevent a violation or dispute. The aim is to minimize opportunities for violations to occur and to provide limitations in carrying out an obligation to the mark. The principle adopted by the Mark registration system in Indonesia is the First to File (constitutive) principle. The Constitutive System is the principle whereby the owner of the rights to a mark that is considered valid is the one who first registers at the Ministry. This system guarantees legal certainty in the form of benefits to registrants (legal owners/holders of Marks) whose trademark registration is accepted as a Mark in the form of a certificate as proof of rights to the Mark as well as being considered the first user of the registered Mark. It is necessary to prove whether the mark registration is done in good or bad faith. In Article 4 paragraph (1) of Law Number Concerning Trademarks and Geographical Indications, that a mark can only be registered on the basis of a request by a brand owner in good faith. The trademark law protects the mark based on Article 21 paragraph 1 explaining that the trademark application will be rejected if the mark has similarities in principle or in whole with the registered mark of another party for similar goods and/or services and a well-known mark owned by another party for goods and/or similar services. Legal protection for brands is regulated based on Law Number concerning Marks and Geographical Indications.